Finding alternatives for the traditional diesel-powered company car: A conjoint analysis approach - De Wilde, Liesbeth; Keserü, Imre; Macharis, Cathy; Vanhaverbeke, Lieselot (Frontiers in Sustainability, 2023)
Although the use of company cars is associated with more congestion, pollution and accidents compared to privately owned cars, the Belgian fiscal system provides exceptionally high incentives to company cars. As a result, the proportion of company cars is higher in Belgium than in any other OECD country. With a corporate mobility budget, more sustainable options are being offered as an alternative to large diesel-powered company cars, but little is known about how company car drivers value these alternatives. In this article, we explore how car-dependent employees make their choices in the company mobility system and aim to find options that enable more sustainable commuting. A choice-based conjoint analysis carried out among 422 car dependent company car drivers revealed that there is currently no alternative that is both more sustainable and more preferred by the sample, which again stresses the need for more drastic government intervention. The results indicate an overall preference for hybrid cars, but a shift towards fully electric vehicles is necessary to have a significant impact on climate change. Our results suggest that respondents with a higher environmental concern are more eager to make the transition towards smaller and fully electric vehicles, which is in line with previous studies.